Optimizing Operation Processes and Supply Chain Management for Enhanced Service and Product Quality in Quick Service Restaurants - Rodriguez, Joel Mark; Reambonanza, Hanna V.; Palallos, Lourdes (UI Scholars Hub, 2025)
Research Aims: The research aimed to identify the relationship between operational processes, supply chain management, and their impact on the quality of service and products in Quick Service Restaurants in the Philippines. It addresses a very critical research gap by providing empirical evidence on how these factors collectively influence business performance. Design/Methodology/Approach: A quantitative research design was used – structured questionnaires were administered to 392 QSR employees and managers working in different locations of the Philippines. Data analysis used correlation, regression, and SEM for robustness. Research Findings: The research proved that sound operational management and supply chain practices improved the quality of services and products. Results were drawn and showed integrated strategies and process optimization in the supply chain drive customer satisfaction and business sustainability. Theoretical Contribution/Originality: The research extended earlier literature demonstrating empirical relationships of operational processes and supply chain management with quality outputs in QSRs, addressing a gap in the Southeast Asian business context. Managerial Implication in the South East Asian Context: The results provided strategic direction for QSR managers to undertake technological adoption, supply chain integration, and process improvements to keep up with competition in the hyper-dynamic market of Southeast Asia. Research Limitation & Implications: Future studies may consider longitudinal research designs to analyse long-term effects, mediating roles of technological innovation, and customer feedback mechanisms.